Necrobiotic granuloma: An update - Achyut Pokharel; Isha Poudel Koirala (Wolters Kluwer Medknow Publications, 2018)
Granulomatous disorders comprise a large family sharing the common histological denominator of granuloma formation. Collagenolytic or necrobiotic granuloma is one in which a granulomatous infiltrate develops around a central area of altered collagen and elastic fibers. The altered fibers exhibit new staining patterns, becoming either more basophilic which gives blue appearance ("blue granuloma") or eosinophilic giving red appearance ("red granuloma"). Conditions which exhibit blue granuloma include granuloma annulare, Wegener's granulomatosis, and rheumatoid vasculitis, whereas red granulomas include necrobiosis lipoidica, necrobiosis xanthogranuloma, rheumatoid nodules, Churg-Strauss syndrome, and eosinophilic cellulitis (Well's syndrome).